Authentic Assessment of Literacy and Numeracy Based on Local Wisdom at Elementary School Level in Ternate City - Ode Zulaeha; Harina Sangadji (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the implementation of authentic assessment of literacy and numeracy based on local wisdom in elementary schools in Ternate City. Methodology: A mixed methods approach was employed involving both qualitative and quantitative data collection. The participants were 200 fifth-grade students from four schools Elementary School 1, Elementary School 2, Islamic Elementary School Nurul Hasan, and Islamic Elementary School Fathul Munir selected proportionally. Data were gathered through classroom observations, documentation, and authentic tasks integrated with local cultural contexts. Qualitative data were analyzed thematically, while descriptive statistics were used for quantitative analysis. Main Findings: The findings reveal that authentic assessment based on local wisdom in Ternate has not yet been systematically implemented in literacy and numeracy learning. However, several innovative teacher practices emerged, such as using the Ternate language for numeracy tasks, conducting literacy activities through interviews with market vendors, and applying mathematical concepts in real-life contexts like market transactions. These practices effectively connected students’ cultural experiences with learning objectives, enhancing engagement and conceptual understanding. Novelty/Originality of this study: The novelty of this study lies in integrating Ternate’s local wisdom as a contextual foundation for authentic literacy and numeracy assessment, bridging the gap between assessment theory and culturally grounded educational practice. The study contributes to the development of context-sensitive assessment instruments that promote equity, relevance, and cultural identity in education. Furthermore, it provides empirical evidence supporting culturally responsive pedagogy as a strategy for improving learning outcomes in diverse local contexts.